DEVELOPMENT OF SPORTS INFRASTRUCTURE IN FERGANA REGION IN THE YEARS OF INDEPENDENCE (Scientific journal of the Fergana State University, 2025)
This article describes the development of sports infrastructure in Fergana region, significant changes during the years of independence. Also, since 1991, the construction of sports facilities, repair and modernization of existing facilities have started in the region. This process served to popularize sports, increase interest in physical education and sports among young people. By the 2000s, sports schools, training centers, modern sports complexes and medical care centers were established in the region. These changes had a positive impact not only on the training of athletes, but also on the development of a healthy lifestyle in society as a whole. It was stated that the sports infrastructure of Fergana region is still developing rapidly and played an important role in increasing the sports potential of the region.